2020
DOI: 10.1161/hypertensionaha.120.15328
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Subclinical Hypercortisolism in Clinical Aldosterone-Producing Adenomas Predicts Lower Clinical Success

Abstract: The clinical characteristics and outcomes in patients with clinical aldosterone-producing adenomas harboring KCNJ5 mutations with or without subclinical hypercortisolism remain unclear. This prospective study is aimed at determining factors associated with subclinical hypercortisolism in patients with clinical aldosterone-producing adenomas. Totally, 82 patients were recruited from November 2016 to March 2018 and underwent unilateral laparoscopic adrenalectomy with at least a 12-month f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 32 publications
3
46
0
Order By: Relevance
“…Lastly, some studies have investigated the genetic mutation of APA with cortisol cosecretion. A recent study based on a Taiwanese database showed that the presence of KCNJ5 mutations was significantly lower among APA patients with subclinical hypercortisolemia than those without ( 15 ). Their immunohistochemistry analysis revealed the lower CYP11B1 expression among KCNJ5 mutated APAs, which generally display a ZF-like phenotype ( 43 ).…”
Section: Cortisol Cosecretion In Primary Aldosteronismmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, some studies have investigated the genetic mutation of APA with cortisol cosecretion. A recent study based on a Taiwanese database showed that the presence of KCNJ5 mutations was significantly lower among APA patients with subclinical hypercortisolemia than those without ( 15 ). Their immunohistochemistry analysis revealed the lower CYP11B1 expression among KCNJ5 mutated APAs, which generally display a ZF-like phenotype ( 43 ).…”
Section: Cortisol Cosecretion In Primary Aldosteronismmentioning
confidence: 99%
“…We restricted studies to those with a sample size ≥10 (to avoid case reports) and written in English. Flow of studies through review and summary of the identified 16 studies are shown in Figure 1A and Table 1 (6,(10)(11)(12)(13)(14)(15)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Cortisol Cosecretion In Primary Aldosteronismmentioning
confidence: 99%
See 2 more Smart Citations
“…The longstanding dogma for targeted therapy for primary aldosteronism has been to pursue curative adrenalectomy for unilateral primary aldosteronism and to prescribe lifelong MR antagonist therapy for bilateral primary aldosteronism (2). It should be noted, that in addition to resolving aldosterone excess, surgical adrenalectomy for primary aldosteronism has the additional advantage of potentially resolving the cortisol excess that is now recognized as a prevalent, and potentially clinically relevant, risk factor (27,46,47,48,49). Below, we discuss the indications and ramifications of surgical adrenalectomy for unilateral, and bilateral, primary aldosteronism, and how these compare to medical therapy.…”
Section: Adverse Health Outcomes In Primary Aldosteronismmentioning
confidence: 99%